Role of metal oxide nanostructures in extracellular pH regulations; AIP Conference Proceedings; Vol. 1760 : Physics of Cancer: Interdisciplinary Problems and Clinical Applications 2016 - Lozhkomoev A. S. Aleksandr Sergeevich (2016, 2016)
Title screen